2006
DOI: 10.1002/ange.200503961
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Macrocyclic Poly(ε‐caprolactone) by Intramolecular Cross‐Linking of Unsaturated End Groups of Chains Precyclic by the Initiation

Abstract: Bioabbaubare cyclische Polyester werden hergestellt, indem eine durch ein cyclisches Zinnalkoxid ausgelöste ε‐Caprolacton‐Polymerisation mit der Zugabe und anschließenden Polymerisation von wenigen Einheiten α‐(1‐Acryloxyethyl)‐ε‐caprolacton gekoppelt wird. Kaulquappenförmige Polyester mit zwei Schwänzen steuerbarer Länge (siehe Bild) sind auf diese Art einfach zugänglich.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…[4] Only a few methods can prepare cyclic polymers with this criterion though various ways have explored the synthesis of cyclic polymers. [17, 2329] Most of the cyclic polymers with narrow polydispersities were prepared by controlled living polymerizations. For example, cyclic [styrene (S)-b-isoprene (I)-b-methyl methacrylate (MMA)] with narrow polydispersity was synthesized under high-dilution conditions by the end-to-end intramolecular amidation reaction of the corresponding linear-α, ω-amino acid precursor [S-b-I-b-MMA] prepared by anionic polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Only a few methods can prepare cyclic polymers with this criterion though various ways have explored the synthesis of cyclic polymers. [17, 2329] Most of the cyclic polymers with narrow polydispersities were prepared by controlled living polymerizations. For example, cyclic [styrene (S)-b-isoprene (I)-b-methyl methacrylate (MMA)] with narrow polydispersity was synthesized under high-dilution conditions by the end-to-end intramolecular amidation reaction of the corresponding linear-α, ω-amino acid precursor [S-b-I-b-MMA] prepared by anionic polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…[8] In this approach, the metal alkoxide initiator remains in the product at the end of the reaction, although recent strategies have been devised utilizing intramolecular cross-linking and elimination of the tin initiator. [8][9][10] Herein, we report a kinetically controlled synthesis of cyclic polyesters of defined molecular weight and narrow molecular weight distribution by the zwitterionic ring-opening polymerization of lactide with N-heterocyclic carbenes (NHCs). Zwitterionic polymerizations, involving chains with a positively and negatively charged group, have been investigated for many years, [11] but typically yield low-molecularweight linear polymers because of the high reactivity of the cationic and anionic chain ends.…”
mentioning
confidence: 99%
“…However, one major drawback of this technique is that the tin alkoxide bond present in the resultant cyclic polymer is unstable and readily undergoes hydrolysis. Li et al [193] reported a refined route to overcome the issue of the liable alkoxide bond by introducing a short block of a photocross-linkable lactone with an acrylate side chain into the polyester macrocycles. After UV crosslinking, the initiator can be removed while the integrity of the macrocyclic structure is maintained.…”
Section: Ring-expansion Approachmentioning
confidence: 99%